2020
DOI: 10.1155/2020/8486129
|View full text |Cite
|
Sign up to set email alerts
|

Food Fortification: The Level of Awareness among Kenyan Consumers

Abstract: More than half of the morbidity and mortality cases among children in Kenya are as a result of micronutrient deficiencies (MNDs). Food fortification is considered by the Government of Kenya as a feasible strategy for addressing MNDs. Worldwide, fortification has been proven to be effective since it does not require any change in dietary habits. Success of large-scale food fortification however may depend on consumer awareness of the fortification benefits. A cross-sectional study was conducted in 13 counties t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The results of this study showed signifi cant levels of food fortifi cation awareness among respondents who attained secondary education and graduation. Similar fi ndings were reported by Linda et al (17) where authors found improved food fortifi cation awareness among respondents with secondary and tertiary level of education. Thus the attainment of higher education can increase the ability to understand and store nutrition information long enough as memory and later use it to a foodrelated decision (18).…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study showed signifi cant levels of food fortifi cation awareness among respondents who attained secondary education and graduation. Similar fi ndings were reported by Linda et al (17) where authors found improved food fortifi cation awareness among respondents with secondary and tertiary level of education. Thus the attainment of higher education can increase the ability to understand and store nutrition information long enough as memory and later use it to a foodrelated decision (18).…”
Section: Discussionsupporting
confidence: 89%